Analisis Nilai Kearifan Lokal Budaya pada Kumpulan Cerita Pendek Kembang Selir Karya Muna Masyari dan Modul Pengajarannya di Kelas XI Sekolah Menengah Atas - Pangestu, Bangkit Aji; Purwanto, Joko; Setyorini, Nurul (Jurnal Bahastra, 2025)
This study aims to describe (1) the values of local cultural wisdom and (2) the design of teaching modules based on the short story collection Kembang Selir by Muna Masyari for eleventh-grade high school students. The primary data source consists of the short story collection Kembang Selir, analyzed through a qualitative descriptive approach using library research techniques. Data were examined through content analysis, while the presentation of findings employed an informal descriptive method. The results of the study indicate that the values of local cultural wisdom reflected in the stories include: (a) human life equipment such as knives, saws, hoes, stoves, cups, pots, and traditional clothing; (b) livelihood systems such as trading and farming; (c) kinship and social systems within community and political structures; (d) language and literature represented through the use of the Javanese language; (e) arts, particularly vocal arts; (f) knowledge systems concerning the natural environment; and (g) religious systems expressed through spiritual rituals. Furthermore, the proposed teaching module for the Kembang Selir short story collection aligns with the Independent Curriculum for Class XI, particularly the learning objective 3.9, which focuses on analyzing cultural values in literature. The implementation employs the Problem-Based Learning (PBL) model to encourage discussion, critical thinking, and contextual understanding.